'Through the looking-glass': addressing methodological issues in analyzing within- and between-sector differences in employee attitudes and behaviors. Issue 6 (2nd November 2021) - Blom, Rutger; Kruyen, Peter M.; van Thiel, Sandra; van der Heijden, Beatrice I. J. M.
Abstract: Many studies have investigated potential differences in employee attitudes and behaviors across sectors. However, empirical evidence in this regard remains largely inconclusive or even contradictory. Although theoretical explanations may exist, it cannot be ruled out that there are issues pertaining to methodological choices at play as well. The aim of this contribution is to explore whether two issues, one related to the justification of interpreting the public sector as a homogenous one and one to controlling for measurement invariance, influence conclusions of comparative research. Using a Dutch data set containing 1, 998 respondents, we tested the impact of these two issues on four concepts that have gotten much attention in employee level comparative research, namely work satisfaction, organizational commitment, proactivity toward self-development, and public service motivation. Our findings demonstrate that differences exist within the public sector and that lack of measurement invariance affects results, which, in turn, affect conclusions regarding within- and between-sector comparisons. We therefore recommend that scholars recognize these issues before conducting comparative research.